Orthogonal Polynomials - 18.2 General Orthogonal Polynomials

From testwiki
Revision as of 11:44, 28 June 2021 by Admin (talk | contribs) (Admin moved page Main Page to Verifying DLMF with Maple and Mathematica)
(diff) ← Older revision | Latest revision (diff) | Newer revision → (diff)
Jump to navigation Jump to search


DLMF Formula Constraints Maple Mathematica Symbolic
Maple
Symbolic
Mathematica
Numeric
Maple
Numeric
Mathematica
18.2.E1 a b p n ( x ) p m ( x ) w ( x ) d x = 0 superscript subscript 𝑎 𝑏 subscript 𝑝 𝑛 𝑥 subscript 𝑝 𝑚 𝑥 𝑤 𝑥 𝑥 0 {\displaystyle{\displaystyle\int_{a}^{b}p_{n}(x)p_{m}(x)w(x)\mathrm{d}x=0}}
\int_{a}^{b}p_{n}(x)p_{m}(x)w(x)\diff{x} = 0
n m 𝑛 𝑚 {\displaystyle{\displaystyle n\neq m}}
int(p[n](x)* p[m](x)* w(x), x = a..b) = 0
Integrate[Subscript[p, n][x]* Subscript[p, m][x]* w[x], {x, a, b}, GenerateConditions->None] == 0
Failure Failure Successful [Tested: 300] Successful [Tested: 300]
18.2.E2 x X p n ( x ) p m ( x ) w x = 0 subscript 𝑥 𝑋 subscript 𝑝 𝑛 𝑥 subscript 𝑝 𝑚 𝑥 subscript 𝑤 𝑥 0 {\displaystyle{\displaystyle\sum_{x\in X}p_{n}(x)p_{m}(x)w_{x}=0}}
\sum_{x\in X}p_{n}(x)p_{m}(x)w_{x} = 0
n m 𝑛 𝑚 {\displaystyle{\displaystyle n\neq m}}
sum(p[n](x)* p[m](x)* w[x], x in X) = 0
Sum[Subscript[p, n][x]* Subscript[p, m][x]* Subscript[w, x], {x, X}, GenerateConditions->None] == 0
Skipped - no semantic math Skipped - no semantic math - -
18.2.E3 x X p n ( x ) p m ( x ) w x = 0 subscript 𝑥 𝑋 subscript 𝑝 𝑛 𝑥 subscript 𝑝 𝑚 𝑥 subscript 𝑤 𝑥 0 {\displaystyle{\displaystyle\sum_{x\in X}p_{n}(x)p_{m}(x)w_{x}=0}}
\sum_{x\in X}p_{n}(x)p_{m}(x)w_{x} = 0

sum(p[n](x)* p[m](x)* w[x], x in X) = 0
Sum[Subscript[p, n][x]* Subscript[p, m][x]* Subscript[w, x], {x, X}, GenerateConditions->None] == 0
Skipped - no semantic math Skipped - no semantic math - -
18.2.E4 x X x 2 n w x < subscript 𝑥 𝑋 superscript 𝑥 2 𝑛 subscript 𝑤 𝑥 {\displaystyle{\displaystyle\sum_{x\in X}x^{2n}w_{x}<\infty}}
\sum_{x\in X}x^{2n}w_{x} < \infty

sum((x)^(2*n)* w[x](<)*infinity, x in X)
Sum[(x)^(2*n)* Subscript[w, x][<]*Infinity, {x, X}, GenerateConditions->None]
Skipped - no semantic math Skipped - no semantic math - -
18.2.E8 p n + 1 ( x ) = ( A n x + B n ) p n ( x ) - C n p n - 1 ( x ) subscript 𝑝 𝑛 1 𝑥 subscript 𝐴 𝑛 𝑥 subscript 𝐵 𝑛 subscript 𝑝 𝑛 𝑥 subscript 𝐶 𝑛 subscript 𝑝 𝑛 1 𝑥 {\displaystyle{\displaystyle p_{n+1}(x)=(A_{n}x+B_{n})p_{n}(x)-C_{n}p_{n-1}(x)}}
p_{n+1}(x) = (A_{n}x+B_{n})p_{n}(x)-C_{n}p_{n-1}(x)
n 0 𝑛 0 {\displaystyle{\displaystyle n\geq 0}}
p[n + 1](x) = (((k[n + 1])/(k[n]))*x + B[n])*p[n](x)- C[n]*p[n - 1](x)
Subscript[p, n + 1][x] == ((Divide[Subscript[k, n + 1],Subscript[k, n]])*x + Subscript[B, n])*Subscript[p, n][x]- Subscript[C, n]*Subscript[p, n - 1][x]
Skipped - no semantic math Skipped - no semantic math - -